Estimating for roadworks using lotus 1-2-3 / Dzulkifli Mohamad - Mohamad, Dzulkifli (1990)
There is no business skill of more importance to construction industry than estimating. Accurate estimates are necessary to the project owner, to the design team, and to construction team. Computer has long been recognised as having great potential in the area of construction estimating. This project has a major objective to aid the reader in both the principle of roadworks estimating and its computer application using LOTUS 1-2-3 version 2.01.